Pengaruh Pemberian Edukasi Tentang Perubahan Seks Sekunder Masa Pubertas Terhadap Pengetahuan Pada Remaja Putri - eka, Yula (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Adolescence is a transition period from children to adults. During this period changes occur, including hormonal, biological, psychological and social changes. These changes happen very quickly and sometimes without us realizing it. The aim of this research was to determine the effect of education about secondary sexual changes during puberty on knowledge among young women at SDN 003 Samarinda. Pre-experimental design method. using the One-group Pretest-posttest design method. The population of this study was 50 teenagers. The samples taken were 30 people, selected by purposive sampling. This research data uses univariate analysis and bivariate analysis using the Wilcoxson test. The results of the research are that there is a relationship between providing education about secondary sexual changes during puberty and knowledge in young women (p-value 0.000). The conclusion is that there is an influence of providing education about secondary sexual changes during puberty on the knowledge of young women at SDN 003 Samarinda. Suggestions: It is hoped that teenagers can be more active in seeking information about puberty from anywhere in order to increase their knowledge and be able to prepare themselves better.